360 Video: A prototyping process for developing virtual reality interventions. Issue 1 (2nd January 2019) - Metsis, Vangelis; Lawrence, Grayson; Trahan, Mark; Smith, Kenneth S.; Tamir, Dan; Selber, Katherine
Abstract: Virtual reality (VR) has emerged as a promising technological intervention for anxiety disorders. However, there are no existing standards and best practices to evaluate the effectiveness of environments to achieve their intervention goals. The purpose of this study was to develop a VR intervention for student veterans with social anxiety disorder and test feasibility utilizing a three-stage development model. The development of a therapeutic VR environment may benefit from an interdisciplinary collaboration of researchers from various fields of study. Utilizing three stages of prototyping with two virtual reality platforms, fully immersive video ( n  = 6) and three-dimensional (3-D) immersive virtual reality ( n  = 8), the research team designed an intervention for student veterans with social anxiety disorder, testing bio-reactivity of participants. Results of prototyping include user feedback validating increased stress levels and increased bio-reactivity specifically in galvanic skin response and heart rate elevation. Implications include the use of 360° video for prototyping 3-D virtual reality interventions.